Analysis of The Readiness of Tan Tao University to Offer an MBA Program - Francisco Tulop Roma; Bernardo Jeffrey Ladao Morante; Maged AlDubai (TTU Review, 2021)
This study provides a strategic analysis on Tan Tao University MBA Program. The main objective of this study is to analyse the readiness of the Tan Tao University to offer an MBA Program and the effectiveness of the curriculum of the proposed MBA Program focusing on four areas such as human resource, facilities and equipment, research aspect and opportunities for development and formulate recommendations based on the ﬁndings that would boost the SBE MBA Program. Data is collected through questionnaire using convenience sampling in order to give a comprehensive view of students and faculty members’ perceptions. Data collected have been presented in tabular forms using weighted mean and percentage to facilitate understanding of the study. Managers of today’s organization must comprehend the essentials of individual and group behaviour if they are to motivate and communicate with others in the organizations. They must understand administrative processes if they are to plan and organize its operations. They must familiarize themselves with mathematical and statistical procedures if they are to efﬁciently control what goes on in an organization. Every company has its leaders and managers. They are the people who get things done, make things happen, and make the decisions that will make the difference between success and failure. It is this special breed of accomplishedprofessionalsforwhomtheGraduateSchoolofBusinessofTanTaoUniversityisdesigned.